Religion and Orientalism in Asian studies - Paramore, Kiri (Bloomsbury Academic, an imprint of Bloomsbury, 2016)
"Religion, and the history of its study in the modern academy, has affected not only the methodologies, but also the disciplinary and regional arrangements of different Asian Studies fields over the past century. Asian Studies has in turn affected, and is increasingly shaping, the study of religion. Religion and Orientalism in Asian Studies looks into this symbiotic relationship - both in current practice, and in the modern histories of both Orientalism and Area Studies. The chapters of the book are integrated by shared themes that run through the past and present practice of Area studies, covering the role of state actors in originating Asian studies, the role of local scholarship in defining and developing it, and the interaction between humanities and social science approaches. Debates over the dominance of Western and/or modern categories and frameworks, the interaction of past and present and the role of religious actors and religious sensibilities in shaping Asian studies, are also covered. Each chapter deals with one regional sub-discipline in Asian studies and is authored by a leading scholar. Shared thematic approaches running through each essay serve to link scholarly approaches in the fields of Chinese studies, Japanese studies, Korean studies, South Asian studies and South East Asian studies"--
Includes bibliographical references
Keywords: Asia -- Study and teaching; Asia -- Religion; Aufsatzsammlung; Religion; Asienforschung